Pepper-pot diagnostic method to define emittance and Twiss parameters on low energies accelerators - Dolinska, M.E.; Doroshko, N.L. (Вопросы атомной науки и техники, 2002)
The new complex mathematical algorithm to determine beam transverse emittance data and the Twiss parameters from intensity measured with pepper-pot diagnostic device on rf low energies accelerators is described.